Changes in indigenous dress and the cocoliztli epidemic of 1544-1548 in New Spain - Oscar René Benavides Cárabes; Carlos Viesca Treviño (Social Medicine Publication Group, 2021)
The changes in indigenous clothing during XVI century Mexico are examined as a factor in the creation of microclimates favorable to vectors of infectious diseases, such as exanthematous typhus, in relation to the cocoliztli epidemic of 1544-48 in New Spain. Key words: Epidemic, cocoliztli, exanthematous typhus, louse, clothing.